Microdous hanlini (Gobiiformes: Odontobutidae), a new species of the fine-toothed sleepers from Guangxi, China - Wang, Fangxin; Wei, Mulan; He, You; Li, Chenhong (Zootaxa, 2024)
Microdous (Gobiiformes: Odontobutidae) is a genus of freshwater sleepers distributed in southern China and Vietnam. There are two described species in this genus, M. chalmersi widely distributed in Hainan Island and Guangxi province of China and M. amblyrhynchos with a very restricted distribution range in Baise, Guangxi. It has been reported that M. chalmersi of Guangxi might be a cryptic species, which is different from M. chalmersi of Hainan. Here, we describe the cryptic species from Guangxi as a new species, Microdous hanlini, and compare it with the other species of Microdous. Microdous hanlini can be distinguished from M. chalmersi by its wider head (head width/head length = 0.51–0.58 vs. 0.48–0.53 in M. chalmersi) and wider interorbital width (interorbital width/head length = 0.15–0.19 vs. 0.09–0.13 in M. chalmersi). Microdous hanlini can be distinguished from M. amblyrhynchos by its longer snout, (snout length/head length = 0.29–0.35 vs. 0.26–0.28 in M. amblyrhynchos); slenderer head (head width/head length = 0.51–0.58 vs. 0.61–0.65); and protruding eyes (vs. not protruding). Phylogenetics analyses based on partial sequence of cytochrome c oxidase subunit I (COI) gene (~1500 bp) showed that M. hanlini, M. chalmersi and M. amblyrhynchos formed reciprocal monophyletic clades and M. hanlini is more closely related to M. amblyrhynchos than to M. chalmersi. Genetic distance between the three species is greater than the interspecific distance between some species of Odontobutis.